Incredible journey: how do developmental signals travel through tissue? - Zhu, A.J.; Scott, M.P. (Genes & Development, 2004)
How developmental signaling proteins traverse tissue during animal development, through or around tightly packed cells, remains an incompletely resolved mystery. Signaling protein movement is regulated to create gradients, control amounts, impose barriers, or provide direction. Signaling can be controlled by the rate of signal production, modification, active transport, trapping along the path, or by the properties of the receptor apparatus. Signals may move by diffusion outside cells, attached to migrating cells, attached to carrier molecules, through cells by transcytosis, along cell extensions, or in released membrane packets. Recent findings about the movement of Hedgehog, Wingless (Wnt), and TGF-beta signaling proteins have helped to clarify the molecular mechanisms used to ensure that developmental signals carry only good news.